The Alien in the Forest OR When Temporal Context Dominates Perception. (November 2014) - Kornmeier, Jürgen; Mayer, Gerhard
Some German hunters came up with pictures taken from a wildlife camera and showing a strange humanoid-like object of about 10 cm size. Its puzzling appearance and a remarkable absence of wildlife in that area after its occurrence triggered paranormal explanations. After reexamination of the pictures, we found a more plausible conventional explanation. This case study serves as an interesting real-world example for the constructive nature of human perception. We discuss how the perceptual system uses spatial and temporal/memory factors to disambiguate ambiguous and restricted sensory information.